Epigenetic regulatory mechanism of ADAMTS12 expression in osteoarthritis - Shu Yang; Xuanping Zhou; Zhen Jia; Mali Zhang; Minghao Yuan; Yizhao Zhou; Jing Wang; Duo Xia (Molecular Medicine, 2023)
Abstract Background Osteoarthritis (OA) is a degenerative joint disease with lacking effective prevention targets. A disintegrin and metalloproteinase with thrombospondin motifs 12 (ADAMTS12) is a member of the ADAMTS family and is upregulated in OA pathologic tissues with no fully understood molecular mechanisms. Methods The anterior cruciate ligament transection (ACL-T) method was used to establish rat OA models, and interleukin-1 beta (IL-1β) was administered to induce rat chondrocyte inflammation. Cartilage damage was analyzed via hematoxylin-eosin, Periodic Acid-Schiff, safranin O-fast green, Osteoarthritis Research Society International score, and micro-computed tomography assays. Chondrocyte apoptosis was detected by flow cytometry and TdT dUTP nick-end labeling. Signal transducer and activator of transcription 1 (STAT1), ADAMTS12, and methyltransferase-like 3 (METTL3) levels were detected by immunohistochemistry, quantitative polymerase chain reaction (qPCR), western blot, or immunofluorescence assay. The binding ability was confirmed by chromatin immunoprecipitation-qPCR, electromobility shift assay, dual-luciferase reporter, or RNA immunoprecipitation (RIP) assay. The methylation level of STAT1 was analyzed by MeRIP-qPCR assay. STAT1 stability was investigated by actinomycin D assay. Results The STAT1 and ADAMTS12 expressions were significantly increased in the human and rat samples of cartilage injury, as well as in IL-1β-treated rat chondrocytes. STAT1 is bound to the promoter region of ADAMTS12 to activate its transcription. METTL3/ Insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2) mediated N6-methyladenosine modification of STAT1 promoted STAT1 mRNA stability, resulting in increased expression. ADAMTS12 expression was reduced and the IL-1β-induced inflammatory chondrocyte injury was attenuated by silencing METTL3. Additionally, knocking down METTL3 in ACL-T-produced OA rats reduced ADAMTS12 expression in their cartilage tissues, thereby alleviating cartilage damage. Conclusion METTL3/IGF2BP2 axis increases STAT1 stability and expression to promote OA progression by up-regulating ADAMTS12 expression.